DNA Polymerase e - More Than a Polymerase. (2003) - Pospiech, Helmut; Syväoja, Juhani E.
Abstract : This paper presents a comprehensive review of the structure and function of DNA polymerase e. Together with DNA polymerases a and d, this enzyme replicates the nuclear DNA in the eukaryotic cell. During this process, DNA polymerase a lays down RNA-DNA primers that are utilized by DNA polymerases d and e for the bulk DNA synthesis. Attempts have been made to assign these two enzymes specifically to the synthesis of the leading and the lagging strand. Alternatively, the two DNA polymerases may be needed to replicate distinct regions depending on chromatin structure. Surprisingly, the essential function of DNA polymerase e does not depend on its catalytic activity, but resides in the nonenzymatic carboxy-terminal domain. This domain not only mediates the interaction of the catalytic subunit with the three smaller regulatory subunits, but also links the replication machinery to the S phase checkpoint. In addition to its role in DNA replication, DNA polymerase e fulfils roles in the DNA synthesis step of nucleotide excision and base excision repair, and has been implicated in recombinational processes in the cell.